O direito à saúde e o acesso a medicamentos: um estudo comparativo entre as jurisprudências brasileira, internacional e estrangeira - Levada, Ana Paula Guarisi Mendes (2014)
The aim of this dissertation is to analyze the right to health, its emergence as a social right, its positivization in our Constitution and its prediction in international organizations. Faced with a historical perspective of the issue, we leave for a practical analysis: the implementation of the right to health with regard to the supply of medicines by the Judicial Courts, in Brazil and abroad. We intend to draw a comparative study among Brazilian and many foreign jurisprudence, with two main purposes: (i) verify the convergence between the Brazilian system and various international and foreign systems and (ii) with the support of foreign jurisprudence, check what are our shortcomings and discover examples in which we can support to improve our system of protection of the right to health